Multi-dimensional Approaches Towards New Technology Insights on Innovation, Patents and Competition (Springer Singapore, 2018)
This open access edited book captures the complexities and conflicts arising at the interface of intellectual property rights (IPR) and competition law. To do so, it discusses four specific themes: (a) policies governing functioning of standard setting organizations (SSOs), transparency and incentivising future innovation; (b) issue of royalties for standard essential patents (SEPs) and related disputes; (c) due process principles, procedural fairness and best practices in competition law; and (d) coherence of patent policies and consonance with competition law to support innovation in new technologies. Many countries have formulated policies and re-oriented their economies to foster technological innovation as it is seen as a major source of economic growth. At the same time, there have been tensions between patent laws and competition laws, despite the fact that both are intended to enhance consumer welfare. In this regard, licensing of SEPs has been debated extensively, although in most instances, innovators and implementers successfully negotiate licensing of SEPs. However, there have been instances where disagreements on royalty base and royalty rates, terms of licensing, bundling of patents in licenses, pooling of licenses have arisen, and this has resulted in a surge of litigation in various jurisdictions and also drawn the attention of competition/anti-trust regulators. Further, a lingering lack of consensus among scholars, industry experts and regulators regarding solutions and techniques that are apposite in these matters across jurisdictions has added to the confusion. This book looks at the processes adopted by the competition/anti-trust regulators to apply the principles of due process and procedural fairness in investigating abuse of dominance cases against innovators.